APPLICATION OF GAMIFICATION IN INTRODUCTION TO PROGRAMMING: A CASE STUDY - Jen, Leong Siok; Said, Siti Hawa Mohamed (PEOPLE: International Journal of Social Sciences, 2019)
Institution of higher educations has struggled to provide engaging method to learn programming although effort has been made by educators but often with limited success. The question is how best to teach introductory to programming for novices students is often not addressed properly. This is because learning programming for college students especially for new learners in programming present many challenges such as subject difficulty, lack of motivation in doing exercises, passiveness in class and diversity of student abilities. Since students often faced a lot of difficulties when learning introductory of programming, gamification has the potential to provide a way to promote students’ motivation and engagement while also providing feedback on the students’ level of competency of the learned material. Gamification is the process of incorporating game elements into education in an effort to increase student engagement.Thus, there appears to be a good fit between introductory of programming and gamification. Taking these elements into consideration, this paper seeks to apply the concept of gamification to semester 1 students taking Java Programming as the first level of programming subject. Some best practices in gamification such as competitions, incorporating engaging games elements, scoring using rewards and levels, badges, providing feedback, and providing homework to encourage informal learning are going to be applied. Finally, several popular online applications such as Kahoot, Online Crossword Puzzle and Online Quiz were also designed to see the impact on these gamification tools towards learning of students. The game would be designed to have 3 levels that increase in difficulties with competition as a core element to increase student’s engagement. This paper would also seeks to design the user evaluation form that can be used to determine the effects of applying gamification on the student’s engagement, motivation level, and understanding of the topic in introductory programming subject. Through the research findings it could provide a platform in formulating alternative ways besides the traditional teaching method for educators in creating educational programming games and applying it to teach novices in introductory programming subjects.